2017
DOI: 10.3775/jie.96.290
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of <i>Chlorella vulgaris</i> in Wastewater Treatment for Biodiesel Production: Growth Optimization and Nutrients Removal Study

Abstract: The environmental footprint for microalgae based biofuel can be reduced by coupling the microalgae cultivation with wastewater treatment. In the present study, the nutrients source for microalga Chlorella vulgaris was replaced by municipal wastewater from wastewater treatment plant located at USM Engineering Campus, Penang. All cultivation experiments were conducted in 5 L photobioreactors (PBRs) under indoor condition with illumination from artificial lights and compressed-air aeration. The growth performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Based on the study by Khoo et al 26 using the same strain of C . vulgaris as in this study, it took around 13 days for the microalgae to reach the stationary phase of growth when it was grown in autotrophic mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study by Khoo et al 26 using the same strain of C . vulgaris as in this study, it took around 13 days for the microalgae to reach the stationary phase of growth when it was grown in autotrophic mode.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra for pure corn starch film showed a broad band occurring around 3,289 cm −1 , which corresponded to the stretching vibration of the -OH group 26 of the vinyl alcohol units and the participation of -OH and -NH 2 bounded hydrogen bonds. 7 The FTIR spectra also revealed that the absorbance of pure corn starch film corresponding to the -OH groups was slightly higher than that of the blends and that of pure PVA films.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…A complete life cycle of microalgae ends within a few days and the cells reproduce themselves using sunlight as a source of energy and carbon dioxide as a source of carbon (44). Moreover, the biomass growth rate can be increased with the addition of specific nutrients and the optimization of aeration (45). Microalgae can be cultivated either in open (environmental) or closed (photobioreactor) systems.…”
Section: Microalgaementioning
confidence: 99%
“…The content of fatty acids also depends on the cultivation conditions and growth phase of microalgae culture (56,57). The essential parameters of choosing microalgae species for biodiesel production are (1) high growth rate (58), (2) content of FFA and TGs (57,59), (3) sensitivity to environmental conditions (temperature, pH, salinity, nutrient intake, illumination) (58), (4) sensitivity to carbon dioxide content and aeration (45), resistance to other microalgae species and/or pathogens (bacteria, fungi, viruses) (60), (5) simple biomass separation and further processing (61), and (6) the possibility of obtaining additional valuable components (50). Many studies compared different microalgae species and suggested useful models of biodiesel production from algal lipids (62-65).…”
Section: Microalgaementioning
confidence: 99%
“…Furthermore, Belkin and Boussiba [10] reported that the growth of Arthospira platensis was inhibited by 50% due to high ammonia concentrations up to 140 mg/L at a pH of 10. Khoo et al [71] reported that the growth of C. vulgaris, which was cultivated on municipal wastewater, was highly influenced by initial pH. Under acidic (pH 2) or alkaline (9 or 11) pH, growth rates were low.…”
Section: Phmentioning
confidence: 99%